Artificial Intelligence and Labor Market Transformations in Latin America - Pablo Egana-delSol; Claudio Bravo-Ortega (Institute of Labor Economics (IZA), 2025)
This study examines the implications of artificial intelligence (AI) on employment, wages, and inequality in Latin America and the Caribbean (LAC). The paper identifies tasks and occupations most exposed to AI using comprehensive individual-level data alongside AI exposure indices. Unlike traditional automation, AI exposure correlates positively with higher education levels, ICT, and STEM skills. Notably, younger workers and women with high-level ICT and managerial skills face increased AI exposure, underscoring unique opportunities. A comparison of LAC with the OECD countries reveals greater impacts of AI in the former, with physical and customer-facing tasks showing divergent correlations to AI exposure. The findings indicate that while AI contributes to employment growth at the top and bottom of wage quintiles, its wage impact strongly depends on the movement of workers from the middle class to below the wage mean of the high-level quintile of wages, hence decreasing the average income of the top quintile.
Keywords: J23; J24; J31; 330; artificial intelligence; automation; labor market; developing economies; AI exposure; inequality; non cognitive skills; cognitive skills